Evaluation of perioperative complications using a newly described staging system for placenta accreta spectrum. (July 2020) - Dall'Asta, Andrea; Calì, Giuseppe; Forlani, Francesco; Paramasivam, Gowrishankar; Girardelli, Serena; Yazbek, Joseph; D'Antonio, Francesco; Bhide, Amarnath; Lees, Christoph C
Abstract: Introduction: The antenatal diagnosis of placenta accreta spectrum (PAS) is in large part subjective and based on expert interpretation. The aim of this study was to externally evaluate a recently developed staging system based on specific and defined prenatal ultrasound (US) features in a cohort of women at risk of PAS undergoing specialist prenatal US, in particular relating to surgical morbidity at delivery. Materials and methods: Database study of cases with confirmed placenta previa. In all, the placenta was evaluated in a systematic fashion. PAS was subclassified in PAS0-PAS3 according to the loss of clear zone, placental lacunae, bladder wall interruption, uterovesical hypervascularity and increased vascularity in the parametrial region. Results: 43 cases were included, of whom 33 had major placenta previa. 31 cases were categorized as PAS0; 3, 4 and 5 cases as PAS1, PAS2 and PAS3, respectively. All women underwent caesarean section and hysterectomy was required in 10. The comparison of the perinatal outcomes among the PAS categories yielded greater operative time (50 (35–129) minutes for PAS0 vs 70 (48–120) for PAS1 vs 95 (60–150) for PAS2 vs 100 (87–180) for PAS3, p < 0.001) and estimated blood loss (800 (500–2500) mls for PAS0 vs 3500 (800–7500) for PAS1 vs 2850 (500–7500) for PAS2 vs 6000 (2500–11000) for PAS3, p < 0.001) for the highest PAS categories, which were also associated with a higher rate of hysterectomy (p < 0.001), blood transfusion (p = 0.002) and admission to ITU or HDU (p < 0.001) and longer postoperative admission of 3 (1–9) days for PAS0 vs 3 (2–12) for PAS1 vs 4.5 (3–6) for PAS2 vs 5 (3–22) for PAS3, p = 0.02. Conclusion: Perioperative complications are closely associated with PAS stage. This information is useful for counselling women and may be important in allocating staff and infrastructure resources at the time of delivery.